The Inventory and Appreciation of Folk Tales on the West Coast of North Sumatra - Fitriani Lubis; Achmad Yuhdi; Ayudia Helmi; Putri Ardiani Lubis (Budapest International Research and Critics in Linguistics and Education (BirLE) Journal, 2022)
Mandailing Natal and Central Tapanuli on the west coast of North Sumatra have a lot of folk tales. The inheritance of folk tales from generation to generation has experienced a shift due to the lack of intensity in speaking across generations, especially the younger generation. Folk tales is increasingly being heard by the younger generation in the villages, including those on the west coast of North Sumatra. The inventory of the legends in the west coast of North Sumatra coast is needed urgently as an effort for the initial step of folk tales documentation. So far, there has not been any research conducted on folk tales in the area. The purpose of this study is to take an inventory of the legends that exist in the west coast of North Sumatra. The method used in the research method is in place (field research). The results showed that there are 12 folk tales, they are The Mystery of the Tortoise Well, The Origin Name of Bangkelang, The Legend of Bukit Bendera, The Aek Busuk, The Giant, The Sacred Urn of Papan Tinggi, The Legend of Ujung Sibolga, The Mystery of Batu Layang, The Legend of Lake Begu, The Origin of Sikaduduak Hill, The Princess Andom Dewi, and The Legend of the Begu Marpayung Forest. Furthermore, these folk tales were packaged into teaching materials for ethnic literature courses at the Indonesian Language and Literature Education Study Program, Unimed. The next stage is the teaching materials are integrated into the Indonesian Language and Literature teaching materials for junior high school students in the west coast of North Sumatra.